Legislative analysis regarding the need to change the legislative framework of pediatric medicines - Niculae, Oana-Raluca; Erimia, Cristina-Luiza (Technium BioChemMed, 2023)
. There is currently a broad consensus that children deserve access to medicines that have been specifically developed and researched for use in young patients. However, until recently, the development and testing of pediatric drugs was far from satisfactory. Although awareness of the lack of satisfactory treatment for children in the EU began to rise in the 1990s, the pharmaceutical industry showed insufficient interest in investing in the development of pediatric medicines. Economic considerations have also been a contributing factor to why companies have refrained from investing proactively in this sector. The fact that children grow and mature means that they are not a uniform subgroup. Therefore, in 2007, the EU introduced a regulation to stimulate the development of medicines for children. In this context, this article aims to examine the regulation of pediatric medicines in the European Union, the impact of this legislation, and the need for future changes to the legislative framework in order to achieve the key objectives of the pharmaceutical strategy for Europe.